2006
DOI: 10.1002/bdra.20294
|View full text |Cite
|
Sign up to set email alerts
|

National estimates and race/ethnic‐specific variation of selected birth defects in the United States, 1999–2001

Abstract: This study can be used to evaluate individual state surveillance data, and to help plan for public health care and educational needs. It also provides valuable data on racial/ethnic patterns of selected major birth defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
483
8
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 594 publications
(544 citation statements)
references
References 25 publications
41
483
8
12
Order By: Relevance
“…Compared with NH-white women, NH-black and Hispanic women had an 81% and 40% lower risk, respectively, of delivering a live born singleton infant with gastroschisis. Although our findings agree with several studies that found a lower risk of gastroschisis among NH-black women (Canfield et al, 2006;Williams et al, 2005), our observation that Hispanic ethnicity is protective was not consistently reported in previous studies. Using popula- tion-based data on nearly 1000 cases from 11 states with active case-finding, Canfield et al (2006) reported that Hispanic women had a significantly higher unadjusted birth prevalence of gastroschisis compared with NHwhite women (PR, 1.25; 95% CI, 1.09-1.43).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Compared with NH-white women, NH-black and Hispanic women had an 81% and 40% lower risk, respectively, of delivering a live born singleton infant with gastroschisis. Although our findings agree with several studies that found a lower risk of gastroschisis among NH-black women (Canfield et al, 2006;Williams et al, 2005), our observation that Hispanic ethnicity is protective was not consistently reported in previous studies. Using popula- tion-based data on nearly 1000 cases from 11 states with active case-finding, Canfield et al (2006) reported that Hispanic women had a significantly higher unadjusted birth prevalence of gastroschisis compared with NHwhite women (PR, 1.25; 95% CI, 1.09-1.43).…”
Section: Discussionsupporting
confidence: 79%
“…Although our findings agree with several studies that found a lower risk of gastroschisis among NH-black women (Canfield et al, 2006;Williams et al, 2005), our observation that Hispanic ethnicity is protective was not consistently reported in previous studies. Using popula- tion-based data on nearly 1000 cases from 11 states with active case-finding, Canfield et al (2006) reported that Hispanic women had a significantly higher unadjusted birth prevalence of gastroschisis compared with NHwhite women (PR, 1.25; 95% CI, 1.09-1.43). Likewise, a study investigating 308 cases in New York reported that, after adjusting for maternal age, Hispanic women were 1.5 times more likely to have an offspring affected by gastroschisis (95% CI, 1.12-2.00; Salihu et al, 2003).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Although there is little information previously published on race/ethnic-or sex-specific prevalence of specific types of CHD to which we can directly compare our results, 19,20 there are published reports on race/ethnicity patterns in general. Canfield et al 8 reported a lower prevalence of tetralogy of Fallot for infants born to Hispanic women compared with infants born to NH-white women; in our study lower prevalence is statistically significant only for Hispanic females. Ferencz et al 26 reported a higher prevalence of both tricuspid valve atresia/ stenosis and pulmonary valve atresia/stenosis for NH-blacks compared with NH-whites; in our study rate ratios for NH-black males and females, pulmonary valve atresia/stenosis-and tricuspid valve atresia/stenosis-affected infants were elevated compared with NH-whites.…”
Section: Original Articlescontrasting
confidence: 56%
“…37 In addition, birth defects registries that only ascertain cases of birth defects in the first year of life exclude infants who died shortly after birth without an autopsy, or diagnosed later in childhood. Moreover, our study only includes live births, whereas other studies 8,12 include data on stillbirths and terminations. Without medical record review, the FBDR data also lack information on case confirmation or case severity.…”
Section: Original Articlesmentioning
confidence: 99%